1981
DOI: 10.1073/pnas.78.9.5682
|View full text |Cite
|
Sign up to set email alerts
|

Insulin is essential for accumulation of casein mRNA in mouse mammary epithelial cells.

Abstract: In the presence of cortisol and prolactin, insulin at concentrations as low as 1 ng/ml significantly stimulates casein synthesis in mammary explants from midpregnant mice; maximal synthesis occurs at 10 ng/ml. However, in the absence of insulin, no detectable immunoprecipitable casein is produced. Insulin also supports enhanced accumulation of casein mRNA in the presence of cortisol and prolactin; neither epidermal growth factor nor somatomedin C has this effect. These inductive actions ofinsulin are not secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
2

Year Published

1982
1982
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 28 publications
0
33
0
2
Order By: Relevance
“…Earlier evidence suggested that addition of prolactin to either explants or dissociated cells from mid-pregnant mouse or rat mammary glands is sufficient to induce the synthesis of casein [7,31], whereas addition of prolactin to mammary explants from mature mouse virgin gland results in increased levels of casein mRNA, but these are not accompanied by an increase in the synthesis of casein unless hydrocortisone is also present [32,33]. More recent evidence suggests that hydrocortisone promotes the accumulation of casein mRNA in mice and rabbits [3,34] whereas insulin promotes both the accumulation of casein mRNA and its subsequent translation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier evidence suggested that addition of prolactin to either explants or dissociated cells from mid-pregnant mouse or rat mammary glands is sufficient to induce the synthesis of casein [7,31], whereas addition of prolactin to mammary explants from mature mouse virgin gland results in increased levels of casein mRNA, but these are not accompanied by an increase in the synthesis of casein unless hydrocortisone is also present [32,33]. More recent evidence suggests that hydrocortisone promotes the accumulation of casein mRNA in mice and rabbits [3,34] whereas insulin promotes both the accumulation of casein mRNA and its subsequent translation [2].…”
Section: Discussionmentioning
confidence: 99%
“…En effet, la suppression transitoire de la prolactine se traduit par une production laitière particulièrement basse (Kann et al, 1978 Bolander et al, 1981 ;Chomczynski et a/., 1984 ;Houdebine et al, 1985a). S'il n'est pas douteux que l'insuline exerce un effet amplificateur puissant sur l'action inductrice de la prolactine, son rôle exact reste mal défini.…”
unclassified
“…It would also explain why diabetic animals show no significant impairment of mammary growth (Norgren, 1968;Topper & Freeman, 1980). In addition to effects on cell replication, Prosser & Topper (1986) (Posner et al, 1974;Campbell et al, 1987 (Bolander et al, 1981;Chomczynski et al, 1984).…”
Section: Insulin-like Growth Factorsmentioning
confidence: 99%
“…Thyroid hormones synergize with pro¬ lactin with respect to a-lactalbumin synthesis (see Topper & Freeman, 1980). Insulin is essential for transcription of mouse and rat casein messenger RNA (Bolander et al, 1981;Chomczynski et al, 1984) but insulin-like growth factors can substitute in other roles, which require supraphysiological insulin concentrations in vitro (see below for further discussion).…”
Section: Culture In Vitromentioning
confidence: 99%